UMPSA and Tianjin University offer Dual Degree programme - Yong, Ying Mei (UMPSA, 2023)
TIANJIN CHINA, 5 December 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) made an official working visit to Tianjin University (TJU) to prepare for the Dual Degree programme between UMPSA and TJU.